Timing precision of the Individual Differences in Dutch Language Skills (IDLaS-NL) test battery - Monen, Janay; Shkaravska, Olha; Withers, Peter; Weustink, Johan; van den Heuvel, Maarten; Trilsbeek, Paul; Dirksmeyer, Reiner; Meyer, Antje S.; Hintz, Florian (Frontiers in Human Neuroscience, 2025)
Online experimentation has become an essential tool in cognitive psychology, offering access to diverse participant samples. However, remote testing introduces variability in stimulus presentation and response timing due to differences in participant hardware, browsers, and internet conditions. To ensure the validity of online studies, it is crucial to assess the timing precision of experimental software. The present study evaluates the Individual Differences in Dutch Language Skills (IDLaS-NL) test battery, a collection of online tests designed to measure linguistic experience, domain-general cognitive skills, and linguistic processing. Implemented using Frinex, a programming environment developed at the Max Planck Institute for Psycholinguistics, IDLaS-NL allows researchers to customize test selections via a web platform. We conducted two studies to assess the timing precision of five chronometric tests within the battery. In Study 1, we evaluated the initial implementation of the tests, analyzing differences between expected and recorded stimulus presentation times, response latencies, and recording delays using the custom-made Web Experiment Analyzer (WEA). The results indicated imprecisions in some measures, particularly for reaction time and audio recording onset. Visual stimulus presentation, on the other hand, was fairly accurate. Study 2 introduced refined timing mechanisms in Frinex, incorporating specialized triggers for stimulus presentation and response registration. These adjustments improved timing precision, especially for speech production tasks. Overall, our findings confirm that Frinex achieves timing precision comparable to other widely used experimental platforms. While some variability in stimulus presentation and response timing is inherent to online testing, the results provide researchers with useful estimates of expected precision levels when using Frinex. This study contributes to the growing body of research on online testing methodologies by offering empirical insights into timing accuracy in web-based experiments.